Pengaruh Profitabilitas, Likuiditas, dan Solvabilitas Terhadap Harga Saham (Studi Empiris Pada Perusahaan Pertambangan Di Bursa Efek Indonesia Tahun 2010-2014) - Azis, Irfan Abdul, Drs. Wiyadi, MM, Ph.D (2016)
The purpose of this study is to analyze and determine the effect Return On Asset (ROA), the Current Ratio (CR), Debt to Equity Ratio (DER) on stock prices. The population in this study are all mining companies that have gone public listed on the Indonesia Stock Exchange in 2010-2014, while the sample selection using purposive sampling. Methods of data analysis using multiple linear regression method. Based on the results of hypothesis testing variable Return On Asset (ROA) positive effect on stock price .. Variable Current Ratio (CR) no positive effect on stock price. Variable Debt to Equity Ratio (DER) positive effect on stock price. Calculated F value of 6.038 means that the model used in this study is right or fit. The coefficient of determination (R2) of 0.117, meaning variation Stock Price variable changes can be explained by the variable of 11.7%. While the rest of 88.3% is explained by other variables outside the model.